Toradora! Vol. 7 - Takemiya, Yuyuko, 1978- (Seven Seas ; Melia [distributor], 2015)
It's taken time, but Ryuji and Taiga have slowly found some common ground and can at least tolerate each other (just a little). The problem is, Fate just doesn't seem to throw Ryuji a bone. Everyone in Ryuji's class is now convinced that he and Taiga are dating--even Minori! And to make matters even more embarrassing, Minori has given Ryuji and Taiga her blessings. How's Ryuji ever going to win Minori's heart now?!